OPTIMALISASI KINERJA JARINGAN WAN PADA PENYEDIA JASA LAYANAN INTERNET MENGGUNAKAN TEKNOLOGI EVPN-MPLS - Adhipramana, Fernanda; Akbar, Yuma (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2023)
An efficient and reliable WAN network is the key to success for modern businesses. With the increasing complexity of the network and the challenges in monitoring BUM traffic (Broadcast, Unkown Unicast, Multicast), a more sophisticated solution is needed. This research focuses on the use of EVPN-MPLS as a superior option for L2VPN technology. Using the Network Development Life Cycle (NDLC) method, this research implements EVPN-MPLS using Juniper devices and conducts performance testing using the PNET-LAB simulation application. The results show that EVPN-MPLS outperforms in terms of latency, jitter, and BUM traffic monitoring. In a testing scenario where one of the PE routers is down, EVPN experiences a packet loss of 4%, while VPLS reaches 12-16%. In addition, the active-active multihoming feature in EVPN-MPLS also offers efficient load balancing and capacity enhancement. Although it requires significant control plane routing resources, EVPN-MPLS promises to improve WAN network performance, especially for internet service providers. This research is expected to provide insights and practical recommendations for those who want to optimize their WAN network management.